Investigation of research on the relationship between early maladaptive schemas and alcohol and substance use disorders - Erbaş, Melda Meliha (Journal of Dependence, 2024)
The aim of this research is to investigate the researches on the relationship between early maladaptive schemas and alcohol and substance use disorders. In this study, which was designed as a case study from qualitative research designs, document review method was used. In line with the purpose of the study, 8 national and 13 international studies were obtained and analyzed in terms of the author and year of publication, type of research, sample, subject and findings. Results show that early maladaptive schemas are directly related to alcohol and substance use. In addition, a limited number of experimental studies examining the effect of schema therapy-oriented interventions also indicate that these interventions have a positive effect on smokers and substance addicts. As a result, it is pointed out in the national and international literature that early maladaptive schemas are associated with alcohol and substance abuse. So, it is thought that it would be useful to disseminate experimental studies examining the effectiveness of schema therapy-oriented interventions on these types of addictions and, in line with the results, to develop schema therapy-based preventive and curative intervention programs aimed at reducing alcohol and substance abuse in adolescents and adults.